Logboats in history: West Highland evidence (Proceedings of the Society of Antiquaries of Scotland, 2000)
This short study re-examines a material culture topic hitherto investigated mainly through archaeology. It is a regional study drawing on lexical and traditional information and adding a dimension to archaeological explanations of the phenomenon of logboats. Modern scholarship suggests that ancient techniques and an ancient boat-type made out of the hollowed trunks of large trees are, according to available evidence and scientific methods of analysis, more modern than ancient. Language and tradition may demonstrably have potential to corroborate this. The significance of terminology and its regional variations is used to exemplify the importance of the concept o/Worter und Sachen or 'words and things' in material culture, a concept that has inspired the collection of dialect vocabularies establishing distribution patterns and linguistic atlases in Europe and especially the Scandinavian countries. Standard dictionaries may often be poor recorders of material culture and this proposition is explored through the subject of logboats.